Rang De Naissance et Intelligence: Un Effort Méthodologique - Laniel, Yvan; Chagnon, Gilles (Canadian Journal of Counselling and Psychotherapy, 2012)
Is the oldest child of a family also the most intelligent? One hundred years of research on the relationship between birth rank order and intelligence have produced many studies whose diverse conclusions do not lend themselves to generalizations. This difficulty lies in the insufficient control of a confusing multitude of variables.In this research, the authors have invested a great deal of effort andattention in their methodology in order to control biases. Although it is fairly simple, the inter-family method has seldom been used in the past. Eighty-four pairs of brothers and sisters from two-child families were compared on the basis of their intellectual superiority.Three statistical analyses, each at three age-difference levels, show that the only instance where the older child would be more intelligent wouldbe when the age difference is no more than 24 months. Les premiers-nés sont-ils les plus intelligents? Cent ans de recherchessur la relation entre le rang de naissance et l'intelligence ont donné lieu à de nombreuses études éparses aux conclusions difficiles à généraliser faute de contrôle adéquat d'une multitude de variables confondantes.Dans cette recherche, les auteurs ont apporté un soin particulier à la rigueur méthodologique pour mieux contrôler les biais. Bien que simple, la méthode "intra-famille" a été peu utilisée dans le passé.Issus de familles de deux enfants, 84 paires de frères ou soeurs ont été comparées sur la base de leur supériorité intellectuelle. Trois analyses statistiques à chacun de trois intervalles d'âge laissent croire que lepremier-né ne serait plus "intelligent" que lorsque l'intervalle d'âge entre enfants d'une même famille ne dépasse pas 24 mois.